Building Information Modelling and Its Application in Digital Architecture to Achieve Sustainability - Asghar Hosseini, Seyed (International Journal of Engineering and Technology, 2018)
Using building information modeling (BIM ) method in architecture can reduce costs and time of project and satisfaction of beneficiaries is provided. By the process in BIM, we can create three-dimensional modeling of building volumes and by the aid of all beneficiaries and executive authorities in project life cycle, we can achieve the best result. The integration and benefits sharing in this method caused that the best quality is considered at proper time and cost. Creating a systematic view in design of a building in which all internal and external beneficiaries can use project executing is a good goal. This study introduced BIM and its application in design and the impact of its use on achieving digital and sustainable architecture of buildings. The introduction of various components of this method with analytical and descriptive approach by evaluation of students all around the world can have a good view of this technique. The increase of perception of authorities of this industry of new technologies of digital design and BIM can improve the culture of construction works in the country and increase economic power. In case of using BIM from the beginning of designing a building and integrating it with digital architecture, we can expect better performance of buildings.Â Â